Energy analysis of poplar production for bioenergy in Sweden. (May 2018) - Nordborg, Maria; Berndes, Göran; Dimitriou, Ioannis; Henriksson, Annika; Mola-Yudego, Blas; Rosenqvist, Håkan
Abstract: Poplar ( Populus spp.) species are currently not widely grown in Sweden but offer interesting options for future large-scale biomass production for bioenergy. This study assesses the average annual net energy yield and the ratio between the gross energy yield and the total primary energy input for well-managed current commercial poplar production systems in Sweden, with and without fertilization with mineral nitrogen (N). The two systems perform similarly, mainly because the yield response to fertilization is estimated to be small. The average annual net energy yields with and without fertilization are estimated at 190 and 179 GJ ha −1 yr −1, respectively. The corresponding energy ratios are 32 and 34, i.e., the total primary energy inputs correspond to only ca. 3% of the gross energy yield, in both cases. Therefore, improving the net energy yield by increasing the harvest level may be considered the most important objective from an energy performance point of view. To do this, more research is needed in order to develop poplar clones that are better adapted to the Swedish climate and identify in which situations poplar responds well to fertilization. At the same time, by reducing the energy inputs associated with the most fuel-intensive activities (wood-chip transportation, chipping, harvesting, forwarding, and stump lifting), greenhouse gas emissions can be reduced. The results should be interpreted with caution since several parameters, especially the yield response to fertilization and fuel consumption rates, are associated with considerable uncertainties. Highlights: Poplar-based bioenergy can contribute to Swedish energy and climate policy goals. Poplar with and without N-fertilization yield on average 190 and 179 GJ ha −1 yr −1 . Energy ratios are 32 and 34 for poplar with and without N-fertilization. The most energy-intensive activities are transport, wood chipping and harvesting. Increasing yield levels is a major option for improving the energy performance.